1988
DOI: 10.1039/an9881300091
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection in the high-performance liquid chromatographic analysis of plant phenolics

Abstract: The electrochemical behaviour of several phenolic compounds of biological interest in vegetable materials was studied. Oxidation potentials of the examined compounds and voltammetric curves of some representative phenols are reported. As a practical application of electrocjremical detection in HPLC, the analysis of monomeric units emanating from nitrobenzene oxidative hydrolysis of wheat straw lignin is described. Electrochemical detection simplifies the analysis, permitting the direct injection of the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Phloroglucinol and 3,5-dihydroxybenzoic acid had a much lower inductive effect on laccase activity than the rest of the compounds studied here, and their addition did not result in any color changes to the culture media. Both these compounds have been reported as weak laccase substrates which cannot be oxidized to quinones because their hydroxyl groups are in the meta position, resulting in a high redox potential (Chiavari et al, 1988). It has been suggested that they can be effective in stabilizing the enzyme, as opposed to having an inductive effect, indicating a potentially important role for these compounds in practical applications (Mai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Phloroglucinol and 3,5-dihydroxybenzoic acid had a much lower inductive effect on laccase activity than the rest of the compounds studied here, and their addition did not result in any color changes to the culture media. Both these compounds have been reported as weak laccase substrates which cannot be oxidized to quinones because their hydroxyl groups are in the meta position, resulting in a high redox potential (Chiavari et al, 1988). It has been suggested that they can be effective in stabilizing the enzyme, as opposed to having an inductive effect, indicating a potentially important role for these compounds in practical applications (Mai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These phenolic compounds can be free phenolic groups in lignin or some of its aromatic degradation products. As an example, the standard potential E 0 of guaiacol amounts to +0.77 V (Chiavari et al 1988). Additional electron releasing groups attached to the guaiacol ring such as methoxy or alkyl groups further reduce its E 0 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] However, anodic detection of NP results in electrode fouling due to the formation of polymeric products on the electrode surface 20) as with other phenols. [21][22][23][24] Accordingly, in terms of the maintenance of electrode surfaces, cathodic reduction is regarded as a much more useful tool for ECD/HPLC analysis of NP than anodic oxidation.…”
Section: Resultsmentioning
confidence: 99%